Comprehensive Analysis of Driver Genes in Personal Genomes of Clear Cell Renal Cell Carcinoma. (19th July 2019) - Li, Jin; Guo, Liping; Chai, Li; Ai, Zisheng
Aim: To characterize personal driver genes in clear cell renal cell carcinoma independent of somatic mutation frequencies. Methods: Personal cancer driver genes were predicted by Integrated CAncer GEnome Score in 417 patients with clear cell renal cell carcinoma using 26 786 somatic mutations from The Cancer Genome Atlas, followed by an integrated investigation on personal driver genes. Results: A total of 233 personal driver genes were determined by Integrated CAncer GEnome Score. The coexpression network analysis found 5 coexpressed modules. The blue module was significantly negatively correlated with all 5 clinical features, including cancer stage, lymph node metastasis, distant metastasis, age, and survival status (death). CTNNB1, TGFBR2, KDR, FLT1, and INSR were the hub genes in the blue module. The expression of 79 personal driver genes was significantly associated with clinical outcomes of patients with clear cell renal cell carcinoma. Conclusions: The set of personal driver genes sheds insights into the tumorigenesis of clear cell renal cell carcinoma and paves the way for developing personalized medicine for clear cell renal cell carcinoma.